The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.3389/fpls.2023.1155170
|View full text |Cite
|
Sign up to set email alerts
|

Methyl jasmonate, salicylic acid, and oxalic acid affects growth, inducible defenses, and pine weevil resistance in Norway spruce

Paal Krokene,
Ketil Kohmann,
Ngan Bao Huynh
et al.

Abstract: The large pine weevil (Hylobius abietis) is a major regeneration pest in commercial forestry. Pesticide application has historically been the preferred control method, but pesticides are now being phased out in several countries for environmental reasons. There is, thus, a need for alternative plant protection strategies. We applied methyl jasmonate (MeJA), salicylic acid (SA) or oxalic acid (OxA) on the stem of 2-year-old Norway spruce (Picea abies) plants to determine effects on inducible defenses and plant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 58 publications
1
2
0
Order By: Relevance
“…The mM1 concentration outperformed, with the highest average at 36.70 cm, while the 3mM concentration showed the lowest average for the trait at 28.41 cm. Some studies have shown that using high concentrations of methyl jasmonate led to significant deterioration in growth characteristics, including a decrease in plant height by up to 39% [15,16]. This result is consistent with previous findings [17,18].…”
Section: Plant Height (Cm)supporting
confidence: 92%
“…The mM1 concentration outperformed, with the highest average at 36.70 cm, while the 3mM concentration showed the lowest average for the trait at 28.41 cm. Some studies have shown that using high concentrations of methyl jasmonate led to significant deterioration in growth characteristics, including a decrease in plant height by up to 39% [15,16]. This result is consistent with previous findings [17,18].…”
Section: Plant Height (Cm)supporting
confidence: 92%
“…Interestingly, we also found a role for JA in the plant growth state at the same time. In previous studies, we found that large amounts of exogenous JA cause stunted plant growth [ 61 ], while moderate amounts promote plant growth [ 62 ]. Even in the JAZ family, there are important genes that can regulate the morphology of the plant and accelerate its flowering [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…On other hand, traumatic resin ducts (TRDs) are typically produced in densely packed, compact bands, displaying distinct distribution patterns (Franceschi et al, 2005;Wu and Hu, 1997). They form as a defensive response to a wide array of both abiotic and biotic stress factors, including mechanical wounds (Gärtner and Heinrich, 2009;Luchi A B et al, 2005;Nagy et al, 2000), insect infestations (Deflorio et al, 2009;Franceschi et al, 2005;Krekling et al, 2000;Nagy et al, 2000), pathogenic fungal invasions (Krokene et al, 2003;Luchi et al, 2005;Mercado et al, 2023), as well as exogenous application of methyl jasmonate (Heijari et al, 2005;Krokene et al, 2023;López-Villamor et al, 2021;Martin et al, 2002).…”
mentioning
confidence: 99%